Microsoft Dynamics GP 2016 cookbook : over 100 powerful and effective recipes to help you solve real-world Dynamics GP problems /: over 100 powerful and effective recipes to help you solve real-world Dynamics GP problems. (2016) - Grieve, Ian; Polino, Mark
No abstract available